Ataxia telangiectasia mutated kinase inhibition promotes irradiation‐induced PD‐L1 expression in tumour‐associated macrophages through IFN‐I/JAK signalling pathway. Issue 2 (16th November 2022) - Gao, Yuke; Li, Yangyi; Lin, Zaihuan; Zeng, Yuxin; Huang, Zhengrong; Han, Linzhi; Zhong, Yahua; Gong, Yan; Wu, Qiuji; Xie, Conghua
Abstract: Tumour‐associated macrophages (TAMs) are one of the primary sources of PD‐L1 expression in the tumour microenvironment (TME). Ionizing radiation (IR) promotes PD‐L1 expression in tumour cells. However, the effect of IR on macrophage PD‐L1 expression and the underlying mechanisms remain unclear. ATM kinase, as the key kinase for initiating DNA damage repair (DDR) process, is associated with innate immune STING axis activation. Here, we explored the molecular mechanism implicated in macrophage PD‐L1 expression regulated by IR as well as the role of ATM kinase in this process. IR‐regulated PD‐L1 expression in macrophages and associated signalling pathways were explored by in vitro studies using murine and human macrophage cell lines. A colorectal xenograft murine model was employed to demonstrate the impact of targeting ATM and PD‐L1 expression in TAMs following IR on growth of tumour in vivo . IR up‐regulated PD‐L1 expression in macrophages, which was further augmented by ATM kinase inhibition. ATM inhibition increased IR‐induced DNA damage, which activated STING/interferon regulatory factor 3 (IRF3) signalling pathway and up‐regulated type I interferon (IFN‐I) expression in macrophages. IFN‐I bound to the IFN α receptor 1 on macrophages, activated the downstream JAK1 and STAT1/3 signalling and eventually led to PD‐L1 up‐expression. ATM inhibition augmented IR‐induced PD‐L1 expression in macrophages and CD8 + T cell infiltration, and promoted anti‐tumour efficacy in vivo. These results suggested that ATM inhibition promoted IR‐induced PD‐L1 expression through the activation of innate immunity in TAMs, which provided a novel approach to enhance the anti‐tumour efficacy of RT. Abstract : ATM inhibition facilitated irradiation‐induced PD‐L1 expression in macrophages by arousing innate immunity through IFN‐I‐JAK1 signaling. ATM inhibitor promoted IR‐induced anti‐tumor efficiency and facilitated cytotoxic T‐cell functions, which provided novel ideas for promoting the anti‐tumor efficiency of IR in colorectal cancer.